Intubation precautions in a pediatric patient with severe COVID-19 (2020)
We present the case of a child diagnosed with COVID-19 soon after open-heart surgery who required an urgent second surgery. The patient suffered from severe COVID-19 disease. The utility of preoperative COVID-19 testing, determination of recovery by an array of inflammatory markers and perioperative management are described.